Magnesium Addition and Treatment of Reinforcement Particles in Al6061 – Sea Sand Composite on Coefficients Friction and Wear Rate - Akbar, Hammar Ilham; Atmaja, Muhammad Ilham Arbi; Surojo, Eko; Kusharjananta, Bambang; Fanani, Reza Aldiansyah (Mekanika: Majalah Ilmiah Mekanika, 2024)
Aluminium matrix composite is a composite material that can be used as reinforcement to increase the tribological properties of composite. The process of manufacturing the Al6061-Sea sand composite used the stir casting method with stirring time of 10 minutes and speed of 600 rpm. Stir casting specimens were manufactured with height dimension of 20 mm and diameter of 10 mm. After that, the specimen was friction tested using the pin on disc method. The highest coefficient of friction was the specimen without electroless coating with the addition of 2 wt% Mg of 0.634. The more mass fraction of sea sand, the higher the porosity, and the lower the density. An electroless coating process can be carried out on reinforcing particles. This study aims to determine the effect of addition of Mg and treatment of reinforcing particles on the Al6061-Sea sand composite on the coefficient of friction and wear rate. The coefficient of friction, the specimen density increased, the porosity and the wear rate, decreased. This occurred because the reinforcement particle size of sea sand bonded strongly to aluminium matrix. The highest coefficient of friction was the electroless coating with the addition of 2 wt% Mg of sea sand, which was 0.646.